Efficacy and safety of wet cupping in the treatment of neurodermatitis: a systematic review and meta-analysis - Zhai, Yan; Hui, You-yi; Jiang, Ze-fei; Ding, Lin; Cheng, Jie; Xing, Tang; Zhai, Han; Zhang, Hong (Frontiers in Medicine, 2024)
BackgroundNeurodermatitis is a chronic skin condition characterized by intense itching and skin thickening due to neurological dysfunction. Its persistent nature poses a challenge to effective treatment, significantly impacting patients’ quality of life. Wet cupping therapy is increasingly being used in clinics to manage neurodermatitis, so it is imperative to assess the evidence regarding its effectiveness and safety.ObjectiveThis review aimed to evaluate the efficacy and safety of wet cupping therapy in patients with neurodermatitis.Methods and analysisRandomized controlled trials (RCTs) investigating wet cupping for neurodermatitis were identified through searches of eight electronic databases and three clinical trial registration platforms from inception to March 2024, using predefined search terms. Included studies underwent quality appraisal using the Cochrane Collaboration’s Risk of Bias Assessment tool. The quality of evidence was assessed independently by two reviewers using the Grading of Recommendations Assessment, Development, and Evaluation System (GRADE). Meta-analysis and publication bias assessment were conducted using ReviewManager 5.4 and STATA 17.0 software, respectively.ResultsThis review encompassed 19 studies, comprising 6 types of comparisons and involving 1,505 participants. The findings revealed no significant difference in the total effective rate between wet cupping alone and high-potency steroids (n = 269, RR = 1.13, 95% CI [0.90, 1.41], p = 0.29, I2 = 83%). However, wet cupping combined with medication or moxibustion exhibited superior efficacy compared to medication alone (n = 272, RR = 1.28, 95% CI [1.16, 1.41], p < 0.00001, I2 = 43%) and (n = 534, RR = 1.22, 95% CI [1.14, 1.30], p < 0.00001, I2 = 0%). Wet cupping groups demonstrated lower recurrence rates (n = 266, RR = 0.31, 95% CI [0.16, 0.60], p = 0.0005, I2 = 0%) and a reduced incidence of adverse events (n = 673, RR = 0.44, 95% CI [0.21, 0.90], p = 0.02, I2 = 36%). Furthermore, wet cupping alone or combined with moxibustion effectively lowered the levels of inflammatory factors compared to medication: TNF-α (n = 120, MD = −6.99, 95% CI [−8.13, −5.85], p < 0.00001, I2 = 0%), IL-1β (n = 120, MD = −5.28, 95% CI [−6.91, −3.65], p < 0.00001, I2 = 48%), and IL-6 (n = 180, MD = −8.61, 95% CI [−13.24, −3.99], p = 0.0003, I2 = 81%).ConclusionThe efficacy of wet cupping therapy is comparable to that of high-potency steroids. Its combined use with medication or moxibustion appears to enhance effectiveness, reduce recurrence rates, and improve safety. However, due to the overall low grade of evidence for the identified outcomes and poor methodological quality, caution is advised when interpreting and applying these findings in clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier: CRD42024524398.